Dielectric and tunability properties of the Pb(Mg1/3Nb2/3)1-xZrxO3 ceramics - Peng, Biaolin; Fan, Huiqing; Li, Q; Zhang, Qi (Elsevier Science B.V., Amsterdam., 2013)
Pure perovskite Pb(Mg1/3Nb2/3)0.8(Sc1/2Nb1/2)0.2O3 ceramics was prepared via a modified “columbite-type” method. The 1:1 B-site ordered structure of Pb(Sc1/2Nb1/2)O3 was detected by XRD and TEM. The dielectric relaxor behavior was described by a Lorentz relation. The dielectric tunability properties were investigated at 300K and 10 kHz. The results show that the ceramics possesses high dielectric tunability (~ 75% at 30 kV/cm), low dielectric loss (~ 0.003) and high figure of merit (~ 250), indicating that it is a promising tunable material. The high dielectric nonlinear behavior was illustrated by employing the Landau-Ginsberg-Devonshire thermodynamic theory and a multipolarization mechanism model. The results indicate that the high non-linearity is related to the contributions of the “extrinsic” polarizations such as the polar nanoregions and nanometer domain wall motions, etc., in addition to the contribution of the “intrinsic” lattice phonon polarization.